Brassica napus Genome Possesses Extraordinary High Number of CAMTA Genes and CAMTA3 Contributes to PAMP Triggered Immunity and Resistance to Sclerotinia sclerotiorum - Rahman, Hafizur; Xu, You-Ping; Zhang, Xuan-Rui; Cai, Xin-Zhong (Frontiers in Plant Science, 2016)
Calmodulin-binding transcription activators (CAMTAs) play important roles in various plant biological processes including disease resistance and abiotic stress tolerance. Oilseed rape (Brassica napus L.) is one of the most important oil-producing crops worldwide. To date, compositon of CAMTAs in genomes of Brassica species and role of CAMTAs in resistance to the devastating necrotrophic fungal pathogen Sclerotinia sclerotiorum are still unknown. In this study, 18 CAMTA genes were identified in oilseed rape genome through bioinformatics analyses, which were inherited from the nine copies each in its progenitors B. rapa and B. oleracea and represented the highest number of CAMTAs in a given plant species identified so far. Gene structure, protein domain organization and phylogentic analyses showed that the oilseed rape CAMTAs were structurally similar and clustered into three major groups as other plant CAMTAs, but had expanded subgroups CAMTA3 and CAMTA4 genes uniquely in rosids species occurring before formation of oilseed rape. A large number of stress response-related cis-elements existed in the 1.5 kb promoter regions of the BnCAMTA genes. BnCAMTA genes were expressed differentially in various organs and in response to treatments with plant hormones and the toxin oxalic acid (OA) secreted by S. sclerotiorum as well as the pathogen inoculation. Remarkably, the expression of BnCAMTA3A1 and BnCAMTA3C1 was drastically induced in early phase of S. sclerotiorum infection, indicating their potential role in the interactions between oilseed rape and S. sclerotiorum. Furthermore, inoculation analyses using Arabidopsis camta mutants demonstrated that Atcamta3 mutant plants exhibited significantly smaller disease lesions than wild-type and other Atcamta mutant plants. In addition, compared with wild-type plants, Atcamta3 plants accumulated obviously more hydrogen peroxide in response to the PAMP chitin and exhibited much higher expression of the CGCG-box-containing genes BAK1 and JIN1, which are essential to the PAMP triggered immunity (PTI) and/or plant resistance to pathogens including S. sclerotiorum. Our results revealed that CAMTA3 negatively regulated PTI probably by directly targeting BAK1 and it also negatively regulated plant defense through suppressing JA signaling pathway probably via directly targeting JIN1.